A Traceable Dna-Replicon Derived Vector to Speed up Gene Editing in Potato: Interrupting Genes Related to Undesirable Postharvest Tuber Traits as an Example - Acha-Beltran, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In potato (Solanum tuberosum L.), protoplast techniques are limited to a few genotypes; thus, the use of regular regeneration procedures of multicellular explants causes us to face com-plexities associated to CRISPR/Cas9 gene editing efficiency and final identification of individuals. Geminivirus-based replicons contained in T-DNAs could provide an improvement to these procedures considering their cargo capability. We built a Bean yellow dwarf virus-derived replicon vector, pGEF-U, that expresses all the editing reagents under a multi-guide RNA condition, and the Green Fluorescent Protein (GFP) marker gene. Agrobacterium-mediated gene transfer experiments were carried out on ‘Yagana-INIA’, a relevant local variety with no previous regeneration protocol. Assays showed that pGEF-U had GFP transient expression for up to 10 days post-infiltration when leaf explants were used. A dedicated potato genome analysis tool allowed for the design of guide RNA pairs to induce double cuts of genes associated to enzymatic browning (StPPO1 and 2) and to cold-induced sweetening (StvacINV1 and StBAM1). Monitoring GFP at 7 days post-infiltration, explants led to vector validation as well as to selection for regeneration (34.3% of starting explants). Plant sets were evaluated for the targeted deletion, showing individuals edited for StPPO1 and StBAM1 genes (1 and 4 lines, respectively), although with a transgenic condition. While no targeted deletion was seen in StvacINV1 and StPPO2 plant sets, stable GFP-expressing calli were chosen for analysis; we observed different repair alternatives, ranging from the expected loss of large gene fragments to those showing punctual insertions/deletions at both cut sites or incomplete repairs along the target region. Results validate pGEF-U for gene editing coupled to regular regeneration protocols, and both targeted deletion and single site editings encourage further characterization of the set of plants already generated. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.